Exhaust Emissions of a CI Engine Operated with Biodiesel from Rapeseed Oil - Aydin, H.; Ilkilic, C. (Taylor & Francis Inc, 2011)
In this study, biodiesel was produced from rapeseed oil and was used in a single cylinder, naturally aspirated and direct-injected diesel engine as pure biodiesel (B100) and as a blend with standard diesel fuel by 20% biodiesel to 80% diesel fuel (B20). The diesel engine emissions and some performance parameters were investigated at fully loaded engine conditions. The effects of pure biodiesel and its blend with diesel fuel on emissions of carbon monoxide (CO), nitrogen oxides (NOx), carbon dioxide (CO2), and sulfur dioxide (SO2) were clarified. Results showed that biodiesel fuel is environmentally friendly since it reduced the emissions of CO, SO2, and CO2 of engines at all speeds. Results also indicated that the pure biodiesel gave about 12% lower power and 20 to 25% higher fuel consumption as compared to diesel. However, the results were almost the same or slightly different from a blend of biodiesel-diesel and petroleum diesel fuel.
Keywords: biodiesel; CI engine; diesel engine; engine performance; exhaust emissions